Strategic Planning of Information Systems and Information Technology by applying the Tozer Methodology to The Lampung Betacom Pawnshop - Florentine, Chelsea; Chernovita, Hanna Prillysca (Journal of Information System and Informatics, 2022)
Betacom is one of the pawnshops established since 2017, which is engaged in the service of distributing loan money to the public based on pawn law with electronic goods guarantees such as mobile phones, laptops, TVs, and so on. In carrying out its business processes, Betacom pawnshops have implemented information systems and information technology but are still not optimal, have not been integrated with each other and are not in line with the mission vision and business strategy of Betacom pawnshops. Therefore, proper strategic planning is needed. This strategic planning will be carried out using the Tozer method, to produce a strategic planning model of information systems that can support and improve the business processes of Betacom pawnshops. This research aims to improve the quality of business processes and SI / IT that can answer solutions to problems that occur. The output resulting from this research is in the form of recommendations for the results of strategic planning of information systems that can be used in the future.